Evaluation of CD4 T lymphocyte cell Levels among Hepatitis B, C and E Viruses negative individuals in Ibadan, Southwestern Nigeria (2017)
Aim: The CD4 T lymphocytes play a key role in achieving a regulated effective immune response to foreign antigens. It is also a valuable parameter for assessing HIV disease progression. However, variations in CD4 T lymphocyte values due to diverse factors have been reported. Here we evaluated CD4 T lymphocytes among community dwellers who tested negative for hepatitis B, hepatitis C and hepatitis E viruses and compared the results with the National Reference Values (NRVs).Study Design: A cross-sectional study was conducted. Participants were enrolled using a convenient sampling technique and their socio-demographic characteristics were captured by administration of semi-structured questionnaires. Place and Duration of Study: This study was conducted among residents of Ibadan metropolis, Southwestern Nigeria. Participants were enrolled between July and September, 2013 at the University College Hospital, Ibadan. Methodology: Four hundred consenting participants who fulfilled the criteria for enrolment were evaluated for CD4 T lymphocyte counts. Results: Estimated mean CD4 T lymphocyte count of 1,183 (CD4 Range: 328-2680) cells/μl of blood was recorded for the participants. Four (1.0%), 151 (37.8%), 157 (39.2%), 74 (18.5), and 14(3.5) of the participants had CD4 T lymphocyte count ranged 352-500, 501-1,000, 1,001-1500, 1501-2,000, and >2,000 cells/μl of blood, respectively. Differences in the estimated mean CD4 count between different age groups varied significantly (P=0.010).Conclusion: In this study, significantly higher CD4 T lymphocyte values were observed among the study population in comparison to the NRVs, and consequently we advise careful interpretation and use of extrapolated CD4 T lymphocyte values in the management of persons with diverse geographical background or health conditions.